2D-statement simulation of thermogasdynamic processes in a rotary-blade engine with external heat supply - Koyokin Vadim; Bulovich Sergey (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
To analyze the characteristics of a rotor-blade engine with external heat supply, a 2D model of this mechanism is considered. The simulation took into account the movement of the working chambers of the engine and the change in their shape. When the chamber came into contact with the gas distribution windows, either gas was transferred to the heat exchangers or the chamber was filled with gas. The formation and development of the jet flow structure in the mass transfer process of an engine – heat exchanger is investigated. The heat transfer process in the engine heat exchangers was modeled using the volumetric heat transfer coefficient, and their hydraulic resistance was also taken into account. The results of the study of heat and mass transfer processes in the engine were presented in the form of cyclograms and indicator diagrams. A comparison was made with the results obtained using the nodal value method.